Beta-Lactam Allergy Association with Surgical Site Infections in Pediatric Procedures: A Matched Cohort Study. Issue 3 (2nd January 2023) - Scaggs Huang, Felicia; Mangeot, Colleen; Sucharew, Heidi; Simon, Katherine; Courter, Joshua; Risma, Kimberly; Schaffzin, Joshua K
Abstract: Background: Little is known about surgical site infection (SSI) risk among pediatric patients with reported beta-lactam allergy (BLA). Methods: We performed a retrospective cohort study at a quaternary children's hospital and compared procedures in patients ages 1–19 years old with and without BLA that required antimicrobial prophylaxis (AMP) during 2010–2017. Procedures were matched 1:1 by patient age, complex chronic conditions, year of surgery, and National Surgical Quality Improvement Program current procedural terminology category. The primary outcome was SSI as defined by National Healthcare Safety Network. The secondary outcome was AMP protocol compliance as per American Society of Health-System Pharmacists. Results: Of the 11 878 procedures identified, 1021 (9%) had a reported BLA. There were 35 (1.8%) SSIs in the matched cohort of 1944 procedures with no significant difference in SSI rates in BLA procedures (1.8%) compared to no-BLA (1.9%) procedures. Tier 3 AMP was chosen more frequently among BLA procedures ( P < .01). Unmatched analysis of all procedures showed that 23.7% of BLA procedures received beta-lactam-AMP (vs. 93.7% of procedures without BLA). There were no major differences in SSI on sensitivity analysis of BLA procedures that did not receive beta-lactam AMP (1.4%) compared to no-BLA procedures with beta-lactam AMP (1.6%). Conclusions: Our retrospective matched analysis of 1944 pediatric procedures found no increase in SSIs in procedures with reported BLA, which differs from studies in adults. We observed that the choice of beta-lactam-AMP was common, even in BLA procedures. More data are needed to delineate an association between non-beta-lactam AMP and SSI in children. Abstract : We performed a retrospective cohort study comparing procedures in patients ages 1–19 years old with and without beta-lactam allergy (BLA) 2010–2017. There was no significant difference in surgical site infection rates in the 1944 procedures matched by BLA status.